PENERAPAN DIET BEBAS GLUTEN BEBAS KASEIN PADA ANAK AUTIS - Oktarina, Ella (Politeknik Kesehatan Kemenkes Bengkulu, 2017)
Gluten-free diet and casein one form of therapy that aims to improve the metabolismof the body with a certain intake of children consumed autism. Gluten and casein in children arenot allowed because of increased bowel permeability. The purpose of this research is to knowthe relationship of nutritional knowledge and maternal obedience in applying a casein-free glutenfree diet in autistic children in Bengkulu City. The research design used was observationalwith Cross sectional study approach. The sample of this research is all mothers who have childrenwho have autism in Bengkulu City as much as 42 respondents, sampling technique in totalsampling. This study is from January to February 2016. Data analysis using chi-square. Therewas no correlation between nutritional knowledge and maternal obedience in applying a caseinfreegluten-free diet in autistic children in Bengkulu City (p = 0,534.) It is recommended thatparents pay attention to nutritional adequacy of the respondents and abstinence ie food sourcesof gluten and casein.